Manifestations of women's superiority in Algerian popular proverbs. (مجلة إحالات, 2026)
This research paper aims to present a study of one of the most important areas of popular literaturethrough analysis, explanation, and inference, which includes studying the effectiveness of Algerian popular proverbs in demonstrating the status of women in society and their superiority, and presentingdemonstrations of their superiority in various areas of social life by classifying these proverbs in the form of semantic fields that show their significance. Its implicit meanings are external understanding and internalmeanings. It also aims to clarify and explain the actual meanings of women’s position in society, which arenot incompatible with the values and teachings of society and religion, by presenting common andcommonly used models.